Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan di UPTD Laboratorium Kesehatan Provinsi Jawa Barat - Sheline Nurpadila Julipani; Zahwa Aulia Syafitri (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
This study aims to determine the effect of service quality on customer satisfaction at the UPTD Health Laboratory of West Java Province. The research method used is a quantitative research method with data collection techniques through observation, interviews, distributing questionnaires and conducting literature studies related to the subject matter. Based on the results of the research, the correlation value (R) of 0.693 means that the influence of Service Quality (variable X) on Customer Satisfaction (variable Y) at the UPTD Health Laboratory of West Java Province can be categorized as strong because it is in the range (0.600-0.799). The results of the simple linear regression analysis show that the coefficient of determination (R Square) is 0.481 or 48.1%, which means that customer satisfaction at the UPTD Health Laboratory of West Java Province is influenced by service quality by 48.1%. While the remaining 51.9% is influenced by other variables or factors outside of service quality.